Can Australian radiographers assess screening mammograms accurately? Biennial follow-up from a four year prospective study and lesion analysis. Issue 3 (August 2016) - Moran, S.; Warren-Forward, H.
Abstract: Introduction: Globally, the role of the radiographer is changing; some countries have developed advanced roles with specific scopes of practice. Other countries, like Australia, are in the process of this change. This paper demonstrates the abilities of Australian radiographers in mammogram screen reading, highlighting some of their specific difficulties with different lesion types. Method: Six experienced radiographers participated in a prospective study, screen reading 2000 mammograms each between 2010 and 2011. This paper looks at the results of those same women at biennial re-screen. Analysis of the results included validation of normal results by negative follow-up screens and new cancers at biennial review; there is also analysis on the types of lesions detected and missed. Results: After biennial review, three cancers in 2013/2014 had been marked as abnormal by one radiographer two years prior, which increased her sensitivity from 64% to 85%. Sensitivity for the radiologists decreased from the assumed 100% to 95%. Radiographers appeared to be skilled in detection of calcifications and architectural distortions but had difficulty with non-specific densities. Conclusion: This study demonstrates the potential for Australian radiographers to enhance the accuracy of screen reading programs. Highlights: Radiographers have the potential to increase breast cancer detection rates. Radiographers appear to be skilled at detecting calcifications. Lesions commonly overlooked by radiographers could be targeted for training.